Sistema de control de riesgos ergonómicos en la práctica odontológica de la Universidad Regional Autónoma de los Andes Uniandes, Matriz Ambato. - Chico Paredes, Gissela Carolina (2018)
The research carried out on the basis of ergonomic risks in dental practice has the fundamental objective of demonstrating that the Ergonomic Risk Control System contributes to improve the dental practice of the Universidad Regional Autónoma de los Andes UNIANDES, Ambato matrix, by applying the Ergonomic Risk Control System. The theoretical framework is based on the operation of the hypotheses that cover the following topics: Ergonomics, Work postures, Identification, Measurement and Evaluation of Ergonomic Risk through the RULA and OCRA methodology, ergonomic risk control, safe work instructions, training program, maintenance, and health monitoring and active breaks. We also included techniques related to dental practice and care protocols for periodontics, endodontics, operative dentistry and surgery, distribution and location in the dental area, considering parameters for work surface, lighting, location of the position, equipment, patient, assistant operator. The methodology is of pre-experimental design, the Quantitative-Deductive method was used, with its steps correspondingly; the population is made up by the students of the career of dentistry from the Universidad Autónoma de los Andes UNIANDES who apply their knowledge, skills and aptitudes through the practice of dental practice in a real situation, these students are in seventh, eighth, ninth and tenth semester, in total 46 people. The alternative guidelines with the application of the RULA and OCRA instruments demonstrated the risk level and with that assessment, they established the Ergonomic Risk Control System, showing a significant decrease in the criticism both in the adoption of forced postures and repetitive movements. A change of attitude was observed in the students, the professors, the Unit of Occupational Safety and Health and the Maintenance Unit of the Institution, who were directly involved in the development of the Control System, which involved health surveillance programs. Safe work instructions, maintenance program, training program and the performance of active breaks. The hypotheses were demonstrated by using the Chi-square test. From the research it is concluded that the Ergonomic Risk Control System improves the dental practice of the students in the seventh, eighth, ninth and tenth semester of dentistry, and it is recommended for them to include the instructions of established works, since this factor will transform them into Professionals carrying out their activities in a safe way, focused on preserving the health status.